2001
DOI: 10.1042/bj3540337
|View full text |Cite
|
Sign up to set email alerts
|

Selective inactivation of guanine-nucleotide-binding regulatory protein (G-protein) α and βγ subunits by urea

Abstract: G-protein-coupled receptors activate signal-transducing G-proteins, which consist of an α subunit and a βγ dimer. Membrane extraction with 5–7M urea has been used to uncouple receptors from endogenous G-proteins to permit reconstitution with purified G-proteins. We show that αi subunits are inactivated with 5M urea whereas the βγ dimer requires at least 7M urea for its inactivation. There is no significant loss of receptors. Surprisingly, Western-blot analysis indicates that the urea-denatured αi subunit remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…To address this issue, disulfide cross-linking studies were also carried out with receptor-containing membranes that had been pretreated with high concentration (5 M) of the chaotropic agent, urea. Previous studies have shown that this strategy leads to the almost complete inactivation or removal of heterotrimeric G proteins, while leaving uncoupled receptors fully functional (35,36 Fig. 8A), in good agreement with previous studies using a similar approach to uncouple heterologously expressed 5-HT 2C receptors (35).…”
Section: Figsupporting
confidence: 79%
See 3 more Smart Citations
“…To address this issue, disulfide cross-linking studies were also carried out with receptor-containing membranes that had been pretreated with high concentration (5 M) of the chaotropic agent, urea. Previous studies have shown that this strategy leads to the almost complete inactivation or removal of heterotrimeric G proteins, while leaving uncoupled receptors fully functional (35,36 Fig. 8A), in good agreement with previous studies using a similar approach to uncouple heterologously expressed 5-HT 2C receptors (35).…”
Section: Figsupporting
confidence: 79%
“…8). Consistent with previous reports (35,36), urea treatment greatly reduced the activity of heterotrimeric G proteins (Fig. 8A), probably due to denaturation of heterotrimeric G proteins and other nonintegral membrane proteins (36).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…An identical cross-linking pattern was obtained, indicating that the presence of peripheral membrane proteins does not influence the ability of C5a receptors to cross-link. Treatment of membranes with urea has been shown to uncouple GPCRs from G proteins yet maintain receptor activity (35,36), thus allowing for functional reconstitution with purified G proteins. Also, 5 M urea treatment can remove InaD, a PDZ domaincontaining scaffold protein, from photoreceptor membranes (37).…”
Section: Resultsmentioning
confidence: 99%